POD analysis of baroclinic wave flows in the thermally-driven, rotating annulus experiment - Stephen, A; Moroz, I; Read, P (1999)
The Proper Orthogonal Decomposition (POD) is a procedure to compute an orthogonal basis from a time series of spatial fields. This basis is optimal among all linear decompositions, in the sense that for a given number of modes, the projection of the original signal onto the subspace will contain the most variance on average. This algorithm is applied to streamfunction fields derived from measurements of the flow in the thermally forced rotating annulus experiment. Results of this analysis are presented, and a method to derive low-dimensional models of the flow by projecting the equations of motion onto these empirical eigenfunctions is discussed.